2012
DOI: 10.1063/1.4767451
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent photoluminescence of ZnO films codoped with tellurium and nitrogen

Abstract: The photoluminescence spectra as well as their temperature dependence of the tellurium and nitrogen (Te-N) codoped ZnO films have been investigated in detail. Explicit evidences of the emissions related to two acceptors [A1: the NO-Zn-Te subunits and A2: the conventional N ions substituting on oxygen sites (NO)] have been found. The acceptor activation energy level of the A1 (∼118–124 meV) is much shallower than that of the A2 (∼224–225 meV) indicating that the A1 should be mainly responsible for the room-temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 101 publications
1
12
1
Order By: Relevance
“…we can get α¼5.7 Â 10 À 4 eV/K and β¼793 K, which are close to the values in literature [26,43]. As clearly shown in Fig.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…we can get α¼5.7 Â 10 À 4 eV/K and β¼793 K, which are close to the values in literature [26,43]. As clearly shown in Fig.…”
Section: Resultssupporting
confidence: 88%
“…Using the values measured at 9 K, the E A is calculated to be $ 126 meV, related to a shallow acceptor state associated with the A 0 X (3.359 eV) and DAP (3.240 eV) emission. Haynes [49] reported that the E loc of the acceptor is proportional to the E A , and the ratio is 0.14 according to our experiment data, in the range of 0.07-0.24 reported before [26,50]. At last, we assign the emission at 3.318 eV to the BX because its intensity decreases with increasing temperature and disappears around 60 K. It is unlikely that D 0 X appears in this energy range, and we ascribe this emission to another A 0 X with E loc ¼ 59 meV, corresponding to a deep acceptor state.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…The system has been used to dope various elements into ZnO films, e.g., gallium [8], nitrogen [9], tellurium [10], manganese [11], and magnesium [12]. The configurations of the system can be thus referenced elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…The codoping experiments show that Te can be helpful in producing intrinsic ZnO thin films [151]. An increased concentration of Te ions into N-doped ZnO films not only made the acceptor energy level shallower but also resulted in improved crystalline quality and efficient suppression of native donor-like defects [152]. Zr-N codoping method was proved to successfully produce p-type ZnO with excellent electrical properties.…”
Section: Other Codopingmentioning
confidence: 98%